2019
DOI: 10.1515/ntrev-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electrochemical performance degradation and catalyst structural parameters on polymer electrolyte membrane fuel cell

Abstract: The catalysts performance degradation is a crucial issue in decay of the polymer electrolyte membrane fuel cell (PEMFC). The effect of Nafion content, dispersity of Pt nanoparticles and selected types of carbon support on the degradation of electrochemical surface area (ECSA) and double layer capacitance (DLC) were experimentally discussed by accelerated stress test (AST). The catalyst with 20wt% Nafion content exhibited better catalyst performance. i.e., the less DLC and ECSA degradation during AST. Catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition to the performance in alkaline media, the performance in acidic media is another major challenge for industrial application. In this study, the electrocatalytic activities of commercial Pt/C and FGN ECSA is another important index to evaluate the stability of catalytic activity [52,54,55]. The CV after long circulation can be used to evaluate the durability of commercial Pt/C and FGN-8 catalysts, with a scan rate of 50 mV s −1 in O 2 -saturated 0.5 M H 2 SO 4 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the performance in alkaline media, the performance in acidic media is another major challenge for industrial application. In this study, the electrocatalytic activities of commercial Pt/C and FGN ECSA is another important index to evaluate the stability of catalytic activity [52,54,55]. The CV after long circulation can be used to evaluate the durability of commercial Pt/C and FGN-8 catalysts, with a scan rate of 50 mV s −1 in O 2 -saturated 0.5 M H 2 SO 4 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…24−26 However, this kind of catalyst also has some limitations such as low stability in an acidic medium (or in the Proton Exchange Membrane Fuel Cells (PEMFC) operation environment). 27 Cutting the quantity of Pt in Ptbased materials with maintaining good catalytic performance is essential for sustainable fuel cell development; this necessitates a high usage of the Pt atoms. To cut the amount of Pt metal and to replace the expensive Pt electrocatalyst, various approaches are used e.g., developing a Pt nanostructure, alloying Pt with some earth abundant metals, metal composites, 28 and so on.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ni, Pd, Ag, Au, and Pt clusters are suitable to catalyze O 2 in their pure form. Wang Y. et al have widely reported that synergistic Mn-Co catalysts act as good ORR catalyts . Many recent articles reveal that metal oxide and sulfide can also be utilized as effective catalysts for the ORR, which gives efficiency close to Pt/C catalysts. However, this kind of catalyst also has some limitations such as low stability in an acidic medium (or in the Proton Exchange Membrane Fuel Cells (PEMFC) operation environment) . Cutting the quantity of Pt in Pt-based materials with maintaining good catalytic performance is essential for sustainable fuel cell development; this necessitates a high usage of the Pt atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the second stage is carried out at low temperatures (LT-WGS) with a highly active catalyst to achieve higher CO conversion. Polymer electrolyte membrane fuel cells (PEMFCs) are a heavily researched topic and an important technology for the future of renewable energy and portable power, as they have the potential to cleanly and efficiently provide electrical energy from hydrogen [1][2][3][4][5][6]. However, these PEMFCs are very susceptible to poisoning by CO, which is a product or byproduct of many hydrogen production reactions (e.g., steam reforming of hydrocarbons or alcohols).…”
Section: Introductionmentioning
confidence: 99%